10z+7=5z+9

Simple and best practice solution for 10z+7=5z+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10z+7=5z+9 equation:


Simplifying
10z + 7 = 5z + 9

Reorder the terms:
7 + 10z = 5z + 9

Reorder the terms:
7 + 10z = 9 + 5z

Solving
7 + 10z = 9 + 5z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-5z' to each side of the equation.
7 + 10z + -5z = 9 + 5z + -5z

Combine like terms: 10z + -5z = 5z
7 + 5z = 9 + 5z + -5z

Combine like terms: 5z + -5z = 0
7 + 5z = 9 + 0
7 + 5z = 9

Add '-7' to each side of the equation.
7 + -7 + 5z = 9 + -7

Combine like terms: 7 + -7 = 0
0 + 5z = 9 + -7
5z = 9 + -7

Combine like terms: 9 + -7 = 2
5z = 2

Divide each side by '5'.
z = 0.4

Simplifying
z = 0.4

See similar equations:

| 16x^2+20x=0 | | (12x-11)(8x-5)=0 | | 3x^2+7x-11=-5x+4 | | x+38=-42 | | 118-4x=4x+14 | | -16x+92=-42 | | 1-y=6 | | 0.2x+1=0 | | -4b-28=0 | | t-(-10)=-8 | | 7x-2y=31 | | 7-63x=12 | | -5-b=2a | | 3x^2-14x=-3 | | -5-b= | | (u)3-7u-6ifu=-2 | | -5-6=2a | | 12x+90=85 | | a+3b=-2 | | 7(y-6)=28 | | 5.6+10.5=2.1A | | 8x^2+22x=-5 | | 11x-20=7x-64 | | -(1-7x)-6(-7-x)=36 | | 7x+35=-21 | | 13+2d+4d+3d+9= | | -16b=9 | | y=x^2-6x-3 | | 26+b=20 | | -8x-9x=.66 | | 2a=18 | | 12=x^2-6x |

Equations solver categories